Clinical Radiographical and Dental Features of a Langerhans Cell Histiocytosis Patient: Comparison of the Preliminary and Fifteenth Year - Huseyin Karayilmaz; Yıldırım Erdogan; Zahit Çiftci; Ayşe Cengiz; Zuhal Kirzioglu (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Oral invovlement in diffuse Langerhans Cell Histiocytosis (LCH) is a rare condition in children. Clinical symptoms are early loss of teeth, pain, gingival selling and oral ulcerations. This case report aims to present and compare the preliminary and fifteenth-year clinical, radiographical and dental features a LCH patient and to suggest principles for long-term dental treatment planning of LCH. A 4. years old LCH patient (with Diabetes Insipidus), with the complaint of nutritional deficiency and chewing difficulties due to early, spontaneous exfoliation of the deciduous teeth as applied. Examinations shoed that deciduous molars ere mobile because of the destruction of supporting aleolar and basal bone. After dental treatments (extractions, restorative treatments etc.), removable space maintainers ere applied. The patient could not attend the following appointments at all. After years, bilaterally, molar open-bite has been detected and orthodontic treatment with orthognathic surgery has been indicated